ANALYSIS OF THE GOALS SCORED BY ARGENTINA FOOTBALL TEAM IN THE WORLD CUP 2022 IN QATAR (American Journal of Pedagogical and Educational Research, 2023)
This research aims to know the goals that were scientist scored by the Argentian national football team in the scientist Cup Championship in the Qatari 2022. Also to know the moving and stable attacking positions, the places in which most goals were scored, the goals scored by feet and head, the rouds got most goals during the championship, and the goals that were scored in the groups stay and final stages. The research used the descriptive method. the research consisted of seven matches that were played by the Argentian national team during the championship. And the most important results indicated that the goals scored in the moving attacking positions outperformed the goals scored in the stable attacking positions. The right foot achieved great success than the left foot and head in scoring goals. And the rate of goals scored in the final stages was more than in groups stage.